Effects of tennis racket swingweight on forehand speed and accuracy in youth players - Nicolau Llull, G.; Delgado García, G. (International Journal of Performance Analysis in Sport, 2024)
Few studies have analysed the effects of the racket inertial parameters on hitting performance in young tennis players. The research aims to study the relationship between the swingweight of the racket and speed and accuracy variables, in young tennis players. Twenty-six players (13.1 ± 2.94 years) performed a forehand hitting test with three rackets of different swingweight (low, medium, and high). Ball speed and hitting accuracy were calculated using a radar, Zepp2 sensor and photogrammetry. Significant differences were found in the ball speed measured by the Zepp2, with the racket with a low swingweight producing a higher speed (p < 0.05; Mean ± SD; 108 ± 43 vs. 102 ± 47 vs. 101 ± 49 km/h, for the racket with a low, medium, and high swingweight). In accuracy, there were significant differences in the absolute longitudinal error, being the racket of the low swingweight the most accurate (182 ± 49 cm vs. 215 ± 88 vs. 208 ± 72 cm; p < 0.05). Also, the low swingweight racket showed higher errors in the net. It is concluded that the lower swingweight racket generates the highest speed values while the error pattern is different between the different swingweights.